The Flow-of-Funds Accounts, the United Nations' System of National Accounts, and the Developing Countries. (IMF Working Papers; Working Paper ;, 1989)
This paper considers flow-of-funds accounting and analysis in relation to the forthcoming revision of the United Nations' System of National Accounts (SNA), with emphasis on the problems faced by developing countries in this area. After a survey of the uses of flow-of-funds data, we conclude that these accounts should continue to have a central place in the SNA. Next, conceptual relations between the SNA and the flow-of-funds accounts are explored as well as the question of harmonization with the Fund's statistical systems. Finally, the feasibility of these accounts for developing countries is demonstrated by a sketch of appropriate estimation procedures.